Synthesis, structural characterization and in vitro anticancer screening of several gold(I) thiolate, dithiocarbonate and dithiocarbamate complexes. (15th September 2022) - Liu, Heng; Tanski, Joseph M.
Graphical abstract: X-ray crystal structures of triphenylphosphine gold(I) thiolate, dithiocarbonate and dithiocarbamate complexes all exhibit linear two-coordinate P-Au-S coordination geometries. The complexes feature various intramolecular gold-oxygen and gold-sulfur contacts and intermolecular gold-sulfur contacts, but no short aurophilic gold–gold contacts are observed. The complexes were accepted for NCI-60 cytotoxicity screenings at the National Institutes of Health Developmental Therapeutics Program and exhibited mild cytotoxicity similar to other known gold(I) phosphine and thiolate complexes. Highlights: New gold(I) compounds were prepared with thiolate, dithiocarbonate and dithiocarbamate ligands. The X-ray crystal structures feature linear two-coordinate gold(I). The complexes feature various intramolecular gold-oxygen and gold-sulfur contacts and intermolecular gold-sulfur contacts, but no short aurophilic interactions. The complexes display mild cytotoxic effects in NCI-60 screenings. Abstract: The crystal and molecular structures of four (triphenylphosphine)-gold(I) complexes synthesized from chloro(triphenylphosphine)-gold(I) and the thiols 5-methyl-1, 3, 4-oxadiazole-2-thiol and 5-methyl-1, 3, 4-thiadiazole-2-thiol, the dithiocarbonate potassium O -isopropyldithiocarbonate and the dithiocarbamate sodium dibenzyldithiocarbamate have been determined. (5-methyl-1, 3, 4-oxadiazole-2-thiolato)-triphenylphosphine-gold(I) (1 ), (5-methyl-1, 3, 4-thiadiazole-2-thiolato)-triphenylphosphine-gold(I) (2 ), ( O -isopropyldithiocarbonato- S )-triphenylphosphine-gold(I) (3 ) and ( N, N -dibenzyldithiocarbamato- S )-triphenylphosphine-gold(I) (4 ) all exhibit a nearly linear two-coordinate gold(I) metal center. The structures of the two thiolate complexes contain similar AuSC angles of 100.86(10)° in (1 ) and 99.51(13)° in (2 ), but different AuSCO/S torsional angles of 36.9(3)° and −15.0(3)°, respectively, highlighting a 3.227(2) Å intramolecular gold-oxygen contact in (1 ) and a 3.2635(11) Å intramolecular gold-sulfur contact in (2 ), the Au ●●● S distance being less than the sum of the Van der Waals radii. The packing in (1 ) features a 4.234(1) Å intermolecular Au ●●● S contact while (2 ) features a very long 4.8408(3) Å gold–gold contact. In the structure of the dithiocarbonate (3 ) the AuSC bond angle of 102.49(14)° is meaningfully larger than the corresponding angle in the structure of the dithiocarbamate (4 ), with an AuSC angle of 98.0(2)°, highlighting an even shorter intramolecular gold-sulfur contact in (4 ) of 3.0120(18) Å which is significantly less than the sum of the Van der Waals radii. The structure of (4 ) is accompanied by nearly planar AuSCS torsional angle of −3.6(4)° and no intramolecular Au ●●● S or Au ●●● Au contacts, while in the dithiocarbonate (3 ) the AuSCS torsional angle of 175.1(3)° reveals the absence of an intramolecular gold-sulfur contact, instead featuring an intramolecular gold-oxygen interaction. Each product was characterized through X-ray crystallography, 1 H, 13 C and 31 P NMR, elemental analysis, IR and MS. In collaboration with the National Institutes of Health (NIH) Developmental Therapeutics Programs (DTP), the complexes have been evaluated for cytotoxic activity against the National Cancer Institute 60 human tumor cell lines screen (NCI-60). The complexes exhibited mild cytotoxicity similar to other known gold(I) phosphine and thiolate complexes.